Role of routine imaging in detecting recurrent lymphoma: A review of 258 patients with relapsed aggressive non‐Hodgkin and Hodgkin lymphoma. Issue 6 (24th February 2014) - El‐Galaly, TC; Mylam, Karen Juul; Bøgsted, Martin; Brown, Peter; Rossing, Maria; Gang, Anne Ortved; Haglund, Anne; Arboe, Bente; Clausen, Michael Roost; Jensen, Paw; Pedersen, Michael; Bukh, Anne; et al.
<x xml:space="preserve">Abstract</x> After first‐line therapy, patients with Hodgkin lymphoma (HL) and aggressive non‐HL are followed up closely for early signs of relapse. The current follow‐up practice with frequent use of surveillance imaging is highly controversial and warrants a critical evaluation. Therefore, a retrospective multicenter study of relapsed HL and aggressive non‐HL (nodal T‐cell and diffuse large B‐cell lymphomas) was conducted. All included patients had been diagnosed during the period 2002–2011 and relapsed after achieving complete remission on first‐line therapy. Characteristics and outcome of imaging‐detected relapses were compared with other relapses. A total of 258 patients with recurrent lymphoma were included in the study. Relapse investigations were initiated outside preplanned visits in 52% of the patients. Relapse detection could be attributed to patient‐reported symptoms alone or in combination with abnormal blood tests or physical examination in 64% of the patients. Routine imaging prompted relapse investigations in 27% of the patients. The estimated number of routine scans per relapse was 91–255 depending on the lymphoma subtype. Patients with imaging‐detected relapse had lower disease burden (P = 0.045) and reduced risk of death following relapse (hazard ratio = 0.62, P = 0.02 in multivariate analysis). Patient‐reported symptoms are still the most common factor for detecting lymphoma relapse and the high number of scans per relapse calls for improved criteria for use of surveillance imaging. However, imaging‐detected relapse was associated with lower disease burden and a possible survival advantage. The future role of routine surveillance imaging should be defined in a randomized trial. Am. J. Hematol. 89:575–580, 2014. © 2014 Wiley Periodicals, Inc.